Prevalence and factors associated with depressive symptomatology in older adults of the “Micaela Bastidas” health center, Lima-Peru: Prevalencia y factores asociados a sintomatología depresiva en adultos mayores del centro de salud “Micaela Bastidas” Lima-Perú - Ponce, Christian (2020)
Objective: To evaluate the factors associated with depression in older adults in a marginal urban area of ​​Peru. Material and methods:  It is a cross-sectional analytical study in adults over 60 years of age in a marginal urban area of ​​Lima. The dependent variable was evaluated using the geriatric depression scale of 15 items, the presence of depression with a score ≥ 6 was considered. The factors associated with depression were calculated using raw and adjusted prevalence ratios with 95% confidence intervals (95% CI) using poisson regressions with robust variance. Results: Of the 142 older adults with an average age and standard deviation was 70.4 ± 8.14. The prevalence of the presence of depression was 55.6% (women 39.6% and men 53.4%). The lack of schooling (RPa: 1.40, 95% CI: 1.04 - 1.88) and not working (RPa: 1.50, 95% CI: 1.09 - 2.05) were risk factors that increased the presence of depression. Conclusion: The prevalence of depression in older adults in a marginal urban area of ​​Peru was high. Older adults who did not complete their schooling and did not work were more likely to develop depression.